Activity of mecillinam against USA urinary tract clinical isolates from 2017 to 2020 including isolates resistant to comparator antibiotics - Stephen Hawser; Ian Morrissey; Nimmi Kothari; Federica Monti; Anne Santerre Henriksen (Journal of Global Antimicrobial Resistance, 2024)
Objectives: To support the clinical development of mecillinam and pivmecillinam in the United States for the treatment of complicated and uncomplicated urinary tract infections (UTIs), this study investigated the activity of mecillinam compared with other antibiotics against Enterobacterales isolates from patients with UTIs in the United States during 2017 to 2020. Mecillinam is a first-in-class amidinopenicillin antibiotic, being the only β-lactam to exert its antibacterial activity through exclusive binding to penicillin-binding protein 2. Pivmecillinam is the oral prodrug of mecillinam and is recommended as a first-line therapy by the Infectious Disease Society of America guidelines for uncomplicated UTIs and is approved for the treatment of uncomplicated UTIs in Europe, Canada, and the United States. Methods: A total of 3303 isolates were collected and antimicrobial susceptibility determined according to Clinical Laboratory and Standards Institute (CLSI) guidelines. Results: Susceptibility was highest for fosfomycin (97.1% susceptible) and mecillinam (94.9% susceptible). Against extended-spectrum beta-lactamase (ESBL)-positive bacteria susceptibilities were highest for mecillinam (98.2% susceptible) and fosfomycin (97.3% susceptible) and against ESBL-positive K. pneumoniae only mecillinam and fosfomycin had > 80% susceptibility. Resistance to comparator antibiotics was highest for trimethoprim-sulfamethoxazole (27.1%), followed by ciprofloxacin (19.3%), ceftriaxone (19.2%), and nitrofurantoin (12.1%). Multi-drug-resistant isolates were most susceptible to mecillinam and fosfomycin. Conclusion: The data further support the clinical development and clinical utility of mecillinam. © 2024 The Author(s). Published by Elsevier Ltd on behalf of International Society for Antimicrobial Chemotherapy.